Sistem Pembinaan Futsal di Bawah Usia 13 Tahun di Club Futsal Se-Kabupaten Kebumen (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The aim of this study was to describe how the coaching system Futsal Club under the age of 13 years throughout the district Kebumen. Approach used in this study is a qualitative approach. The method used include interviews, observation, and documentation. The subject of this research is all personal involved and can be used as a source of data to determine the required information. The object of this research is everything related managerial Young Swallow Futsal Academy, Perseka Filfa futsal, and futsal. Analysis of the data in this study is to collect data, sorting the data, studying the data, describing data and make final analyzes. This results research is the management of organization management, handling the management of athletes and coaches at the club futsal management under the age of 13 years se-Kebumen district have said well. Management infrastructure and management coaches are already well underway. Overall management process futsal club se under the age of 13 years can be said to be good Kebumen district.